Halogen-containing hydro-upgrading catalyst, preparation method and application

By introducing halogen into the hydrogenation modification catalyst, the strong acid strength is reduced and the medium-strong acid density is increased, the problem of excessive cracking of the catalyst during the hydrogenation modification process is solved, and the hexadecane number and hydrogenation depth of the diesel fraction are significantly improved.

CN119633880APending Publication Date: 2025-03-18CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411817857.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing hydrogenation modification catalysts are over-cracked during the hydrogenation modification process, resulting in the inability to effectively increase the cetane number of the diesel fraction.

Method used

By introducing halogen into the catalyst, appropriately toxic the catalyst, reducing the strength and acid amount of strong acid, thereby increasing the medium-strong acid density, reducing branched chain generation, avoiding excessive cracking, and cooperating with the supported hydrogenation active metal.

Benefits of technology

Significantly increase the cetane number of the diesel fraction, keep the side chains on the ring free from damage, increase the hydrogenation depth, and reduce the diesel density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182317200000091
    Figure BDA0005182317200000091
  • Figure HDA0005182317210000011
    Figure HDA0005182317210000011
Patent Text Reader

Abstract

The invention provides a halogen-containing hydro-upgrading catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) uniformly stirring pseudo-boehmite, an extrusion aid, a molecular sieve and optional amorphous silica-alumina to obtain mixed powder; (2) adding halogen-containing inorganic acid into the mixed powder obtained in the step (1), uniformly mixing and kneading, performing extrusion molding in a banded extruder, and drying and roasting to obtain a carrier; and (3) impregnating the carrier obtained in the step (2) in a solution formed by a hydrogenation active metal precursor, impregnating hydrogenation active metal by a complexing impregnation method, and drying to obtain the catalyst. According to the method, halogen is introduced into the carrier, the density of medium-strong acid is increased, the possibility of rearrangement and isomerization of carbocations is reduced, the generation of branched chains is reduced, the problem of excessive cracking is avoided, and the cetane number of the diesel fraction can be remarkably increased in the direct coal liquefaction oil hydrogenation modification process through synergistic matching with loaded hydrogenation active metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogenation catalyst and a preparation method and application thereof, in particular to the field of fixed-bed coal direct liquefaction oil hydrogenation catalyst preparation. The catalyst and preparation method of the present invention have practical and broad applications on various types of supported catalysts in reactions such as coal tar hydrogenation. Background Art

[0002] Coal direct liquefaction oil has the characteristics of high density, high heat capacity, high cycloalkane content, and low aromatic content. The diesel produced has a low freezing point and high calorific value, but the diesel component has a low content of straight-chain alkanes, a high content of cycloalkanes, and a low cetane number, which limits its application in the diesel direction. The selective hydrogenation and ring opening of polycycloalkanes using hydro-modification technology can effectively improve the cetane number of diesel. The generated alkanes have the characteristics of few branches, few rings, and long side chains. However, the strong acid density of the hydro-modification catalyst currently used is large, and the ratio of medium-strong acid / strong acid is ≤1.0. During the hydro-modification process, the cycloalkane ring is opened and the side chain is also broken. This excessive cracking ability leads to the inability to effectively improve the cetane number of the diesel fraction. Efficiently converting the cycloalkane structure in the feedstock oil while retaining the side chains on the ring as much as possible is an important issue faced by the development of hydro-modification catalysts.

[0003] At present, there are two ways to improve the cetane number: on the one hand, the hydrogenation function is enhanced by loading a suitable proportion of hydrogenation active metals to exert the metal catalytic function and hydrogenate the aromatic ring into a cycloalkane ring; on the other hand, the strong acid is appropriately weakened. Since the strong acid is too strong, the side chains on the ring will also crack while opening the ring, and the cetane number will decrease. Therefore, it is necessary to increase the amount of medium-strong acids and increase the ratio of medium-strong acids to strong acids.

[0004] Halogens can form weaker acid centers with alumina carriers, promote the adsorption of hydrogen by the catalyst, enhance the hydrogenation function of the catalyst, and promote the hydrogenation ring opening of aromatics; at the same time, halogens have a positive carbon effect on carbon cations, improve the stability of carbon cations through p-π conjugation, reduce the possibility of rearrangement isomerization, and reduce the formation of side chains, thereby improving the cetane number. Summary of the invention

[0005] The strong acid density of the hydro-modification catalyst currently used is large. During the hydro-modification process, the ring is opened and the side chain is broken. Excessive cracking causes the cetane number of the diesel fraction to be unable to be effectively improved. Efficiently converting the cycloalkane structure in the feedstock oil while keeping the side chains on the ring as intact as possible is an important issue faced in the development of hydro-modification catalysts.

[0006] At present, there are two ways to improve the cetane number: on the one hand, the hydrogenation function is enhanced by loading a suitable proportion of hydrogenation active metals to exert the metal catalytic function and hydrogenate the aromatic ring into a cycloalkane ring; on the other hand, the strong acid is appropriately weakened. Since the strong acid is too strong, the side chain on the ring will also crack while opening the ring, and the cetane number will decrease. Therefore, it is necessary to increase the number of medium-strong acids and increase the ratio of medium-strong acids to strong acids. The appropriate addition of halogens can meet both of these requirements at the same time, promote the catalyst to adsorb hydrogen, enhance the catalyst's hydrogenation function, and convert the strong acid into a weaker medium-strong acid to avoid excessive cracking.

[0007] Aiming at the problem that the strong acid density of the hydro-reforming catalyst rich in cycloalkyl oil is large and the cetane number cannot be effectively improved due to excessive cracking, the present invention provides a halogen-containing hydro-reforming catalyst, a preparation method and application thereof. The method introduces halogen into a carrier, appropriately poisons the catalyst, reduces the strength and acid amount of the strong acid, thereby increasing the density of the medium-strong acid, reducing the possibility of carbon cation rearrangement isomerization, reducing the generation of branched chains, avoiding the problem of excessive cracking, and synergizing with the loaded hydrogenation active metal to significantly improve the cetane number of the diesel fraction.

[0008] According to a first aspect of the present invention, there is provided a method for preparing a halogen-containing hydro-reforming catalyst, the method comprising the following steps:

[0009] (1) mixing pseudo-boehmite, an extrusion aid, a molecular sieve, and optionally amorphous silicon-aluminum to obtain a mixed powder;

[0010] (2) adding a halogen-containing inorganic acid to the mixed powder obtained in step (1), kneading the mixture evenly, extruding the mixture into strips in an extruder, and drying and calcining the mixture to obtain a carrier;

[0011] (3) impregnating the support obtained in step (2) in a solution formed by a hydrogenation active metal precursor, impregnating the hydrogenation active metal by a complex impregnation method, and obtaining a catalyst after drying.

[0012] Wherein, in step (1), based on the total weight of the mixed powder, the content of pseudo-boehmite is 40wt% to 75wt%; the content of amorphous silica-alumina is 0wt% to 20wt%; the content of the extrusion aid is 1wt% to 10wt%; the content of the molecular sieve is 15wt% to 55wt%;

[0013] In step (2), the amount of the halogen-containing inorganic acid used is 0.2 wt% to 0.5 wt% of the mixed powder.

[0014] Preferably, in step (3), the hydrogenation active metal is nickel and one or two selected from molybdenum and tungsten.

[0015] Preferably, based on the total weight of the catalyst, calculated as the respective oxides,

[0016] The content of nickel is 1wt% to 10wt%; the content of molybdenum and tungsten is 10wt% to 40wt% in total.

[0017] It should be noted that, in this document, 0 wt % means that the component does not exist.

[0018] Preferably, the extrusion aid is one or more selected from carboxymethyl cellulose, citric acid, sesbania powder and guar gum.

[0019] Preferably, in step (1), based on 100 wt % of the mixed powder, the content of pseudo-boehmite is 50 wt % to 70 wt %.

[0020] Preferably, in step (1), the molecular sieve is one or more selected from the group consisting of Y-type molecular sieve, β molecular sieve and SAPO-11 molecular sieve.

[0021] Preferably, the silicon-aluminum molar ratio of the Y-type molecular sieve is 3-60, more preferably 5-30, and even more preferably 6-12.

[0022] Preferably, based on 100wt% of the mixed powder, the dry basis content of the Y-type molecular sieve is 10wt% to 50wt%, more preferably 20wt% to 45wt%, and even more preferably 25wt% to 40wt%.

[0023] Preferably, the silicon-aluminum molar ratio of the β molecular sieve is 20-45, preferably 25-40.

[0024] Preferably, based on 100 wt % of the mixed powder, the dry basis content of the β molecular sieve is 0 wt % to 10 wt %, and more preferably 2 wt % to 8 wt %.

[0025] Preferably, the silicon-aluminum molar ratio of the SAPO-11 molecular sieve is 0.4 to 0.7, preferably 0.45 to 0.6.

[0026] Preferably, based on 100 wt % of the mixed powder, the content of the SAPO-11 molecular sieve is 0 wt % to 10 wt %, and more preferably 1 wt % to 8 wt %.

[0027] Preferably, in step (2), the halogen-containing inorganic acid is one or more selected from hydrofluoric acid, hydrochloric acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hydrobromic acid and hydroiodic acid.

[0028] Preferably, the concentration of the halogen-containing inorganic acid is 1 wt% to 10 wt%.

[0029] In step (2), the extrusion molding method can adopt the method disclosed in the prior art, and the shape can be cylindrical strips, clover, etc.

[0030] Preferably, in step (2), the drying and calcining is to dry the formed carrier at 60-90°C for 0.5-3h, then dry it at 100-160°C for 0.5-3h, and then heat it to 500-700°C at a heating rate of 1-10°C / min and keep it at that temperature for 1-5h to obtain the carrier.

[0031] Preferably, in step (3), the hydrogenation active metal is nickel and one or two selected from molybdenum and tungsten.

[0032] Preferably, the hydrogenation active metal precursor is selected from one or more of nickel nitrate, nickel sulfate, basic nickel carbonate, molybdenum oxide and ammonium metatungstate.

[0033] The solution of the hydrogenation active metal precursor is an aqueous solution of the hydrogenation active metal precursor or an aqueous solution of the hydrogenation active metal precursor formed under acidic conditions.

[0034] Based on the total weight of the catalyst, the nickel content is 1wt% to 10wt%, and the molybdenum and tungsten content is 10wt% to 40wt% in total, preferably 15wt% to 35wt%, and more preferably 20wt% to 30wt%, calculated as their respective oxides.

[0035] In step (3), the specific operation steps of the complex impregnation can refer to the reports of the prior art. For example, a given amount of nickel and one or two metal precursors selected from molybdenum and tungsten and citric acid are first dissolved in a certain amount of deionized water, and then impregnated on the support of step (2) overnight by an equal volume method. For specific operations, please refer to the literature:

[0036] Cheng Lijun, Liu Zhao, Yuan Shanliang, et al., Ag-Mn / γ-Al2O3-TiO2 catalyst prepared by citric acid complex impregnation method for propane catalytic combustion[J]. Journal of Fuel Chemistry and Technology, 2019, 47(11): 1379-1385.

[0037] In the above step (3), the drying is to dry the carrier after impregnation with the hydrogenation active metal at 60-90°C for 0.5-3h, and then dry it at 100-160°C for 0.5-3h.

[0038] According to a second aspect of the present invention, a halogen-containing hydro-reforming catalyst is provided, which is prepared by the method for preparing a halogen-containing hydro-reforming catalyst according to the present invention.

[0039] Preferably, in the NH3-TPD test, the ratio of the peak area integration in the range of 200 to 400°C to the peak area integration in the range of more than 400°C is 1.3 to 1.9.

[0040] According to a third aspect of the present invention, there is provided a method for direct liquefaction of coal by hydro-upgrading, which comprises the following steps:

[0041] a) placing the halogen-containing hydro-upgrading catalyst according to the present invention in a sulfided state;

[0042] b) subjecting the coal direct liquefaction oil to a hydrogenation reaction with hydrogen in the presence of the halogen-containing hydro-upgrading catalyst in a sulfided state obtained in step a).

[0043] The halogen-containing hydro-reforming catalyst according to the present invention can be put into a sulfided state by a wet sulfidation method well known to those skilled in the art, for example, wet sulfidation is carried out at 250-300°C.

[0044] Preferably, the hydrogenation reaction conditions in step b) are: reaction temperature 340-360°C, total reaction pressure 12-14 MPa, liquid hourly volume space velocity 2-3 h -1 , hydrogen to oil volume ratio is 500~1000.

[0045] According to the NH3-TPD test, the halogen-containing catalyst according to the present invention has a higher ratio of medium-strong acid to strong acid compared with the halogen-free catalyst according to the temperature range, while the medium-strong acid to strong acid ratio of the halogen-free catalyst is close to 1; and the peak of the catalyst according to the present invention shifts to low temperature, showing weaker acidity, which can effectively avoid the occurrence of chain breaking reaction. This is attributed to the halogen forming a weaker acid with the aluminum oxide in the carrier, thereby weakening the strong acid and increasing the proportion of medium-strong acid.

[0046] Compared with the catalysts in the prior art, the diesel fraction obtained by the halogen-containing catalyst according to the present invention has a lower density and a higher hydrogenation depth, which is attributed to the fact that an appropriate amount of halogen promotes the adsorption of hydrogen by the catalyst; the predicted cetane number is larger, indicating that during the hydrogenation and reforming process, the side chains on the ring are retained or the long carbon chains are not rearranged, which is attributed to the fact that the halogen weakens the strong acid in the catalyst, stabilizes the carbon cations, and avoids excessive cracking or rearrangement. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 NH3-TPD spectra of Examples 1 to 6 and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0048] The present invention is further described below through specific embodiments. The following description is only exemplary and does not limit the protection scope of the present invention.

[0049] Example 1

[0050] The chlorine-containing hydro-reforming catalyst is prepared by the following steps:

[0051] a. First, based on the mass of the mixed powder, 51wt% pseudo-boehmite, 10wt% amorphous silica-alumina, 1wt% sesbania powder, 2wt% citric acid, 30wt% Y-type molecular sieve with a silicon-aluminum ratio of 10, 4wt% β molecular sieve with a silicon-aluminum ratio of 35, and 2wt% SAPO-11 molecular sieve with a silicon-aluminum ratio of 0.5 were stirred to obtain a mixed powder;

[0052] b. Then, 6wt% hydrochloric acid is added to the mixed powder, the amount of acid used accounts for 0.35wt% of the mixed powder, and the mixture is kneaded evenly, and extruded into a cylindrical strip in an extruder. The formed carrier is dried at 80°C for 1h, then dried at 120°C for 2h, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 3h for roasting to obtain the carrier.

[0053] c. A complex impregnation method is adopted on the carrier. Based on the total weight of the carrier, 7.2% basic nickel carbonate, 35.3% ammonium metatungstate, and 3% citric acid are dissolved in a certain amount of deionized water, and impregnated on the carrier of step b overnight by an equal volume method, corresponding to 3wt% nickel and 28wt% tungsten in terms of oxide. The carrier after impregnation with the hydrogenation active metal is dried at 80°C for 2h and then dried at 120°C for 2h to obtain a catalyst.

[0054] Example 2

[0055] The bromine-containing hydro-reforming catalyst is prepared by the following steps:

[0056] a. First, based on the mass of the mixed powder, 50wt% pseudo-boehmite, 5wt% amorphous silica-alumina, 2wt% sesbania powder, 3wt% citric acid, 5wt% guar gum and 35wt% Y-type molecular sieve with a silica-alumina ratio of 12 were uniformly stirred to obtain a mixed powder;

[0057] b. Then, 8 wt% hydrobromic acid is added to the mixed powder, the amount of acid used accounts for 0.3 wt% of the mixed powder mass, and the mixture is kneaded evenly, and extruded into cylindrical strips in an extruder in a manner disclosed in the prior art. The formed carrier is dried at 90° C. for 1 h, then dried at 130° C. for 3 h, and then heated to 500° C. at a heating rate of 6° C. / min and kept warm for 5 h for roasting to obtain the carrier.

[0058] c. The hydrogenation active metal was impregnated according to the method of step c of Example 1, except that the precursors were nickel nitrate and ammonium metatungstate, and 5wt% nickel and 20wt% tungsten were impregnated as oxides. The carrier impregnated with the hydrogenation active metal was dried at 90°C for 0.5h and then at 120°C for 3h to obtain a catalyst.

[0059] Example 3

[0060] The iodine-containing hydro-reforming catalyst is prepared by the following steps:

[0061] a. First, based on the mass of the mixed powder, 50wt% pseudo-boehmite, 1wt% sesbania powder, 4wt% carboxymethyl cellulose, 35wt% Y-type molecular sieve with a silicon-aluminum ratio of 3, and 10wt% beta molecular sieve with a silicon-aluminum ratio of 25 were uniformly stirred to obtain a mixed powder;

[0062] b. Then, 1 wt% hydroiodic acid is added to the mixed powder, the amount of acid used accounts for 0.5 wt% of the mixed powder mass, and the mixture is kneaded evenly, and extruded into a cylindrical strip in an extruder in a manner disclosed in the prior art. The formed carrier is dried at 60° C. for 3 h, then dried at 160° C. for 0.5 h, and then heated to 700° C. at a heating rate of 10° C. / min and kept warm for 1 h for roasting to obtain the carrier.

[0063] c. The hydrogenation active metal was impregnated according to the method of step c of Example 1, except that the precursors were basic nickel carbonate and ammonium metatungstate, and 1wt% nickel and 30wt% tungsten were impregnated as oxides. The carrier impregnated with the hydrogenation active metal was dried at 60°C for 3h and then at 100°C for 3h to obtain a catalyst.

[0064] Example 4

[0065] The fluorine-containing hydro-reforming catalyst is prepared by the following steps:

[0066] a. First, based on the mass of the mixed powder, 75wt% of pseudo-boehmite, 5wt% of guar gum powder, 5wt% of citric acid, 10wt% of Y-type molecular sieve with a silicon-aluminum ratio of 60, and 5wt% of SAPO-11 molecular sieve with a silicon-aluminum ratio of 0.45 were stirred to obtain a mixed powder;

[0067] b. Then, hydrofluoric acid with a concentration of 1.5 wt% is added to the mixed powder, and the amount of the acid accounts for 0.2 wt% of the mixed powder mass. The mixture is kneaded evenly, and extruded into a cylindrical strip in an extruder in a manner disclosed in the prior art. The formed carrier is dried at 90° C. for 0.5 h, then dried at 100° C. for 3 h, and then heated to 500° C. at a heating rate of 1° C. / min and kept warm for 1 h for roasting to obtain the carrier.

[0068] c. The hydrogenation active metal was impregnated according to the method of step c of Example 1, except that the precursors were nickel sulfate and molybdenum oxide, and 10 wt% nickel and 40 wt% molybdenum were impregnated as oxides. The carrier impregnated with the hydrogenation active metal was dried at 90° C. for 0.5 h, and then dried at 160° C. for 0.5 h to obtain a catalyst.

[0069] Example 5

[0070] The chlorine-containing hydro-reforming catalyst is prepared by the following steps:

[0071] a. First, based on the mass of the mixed powder, 40wt% pseudo-boehmite, 20wt% amorphous silica-alumina, 1wt% guar gum powder, 2wt% citric acid, 3wt% sesbania powder, 4wt% carboxymethyl cellulose, 18wt% Y-type molecular sieve with a silicon-aluminum ratio of 8, 2wt% β molecular sieve with a silicon-aluminum ratio of 45, and 10wt% SAPO-11 molecular sieve with a silicon-aluminum ratio of 0.6 were stirred to obtain a mixed powder;

[0072] b. Then, hypochlorous acid with a concentration of 10 wt% is added to the mixed powder, the amount of acid used accounts for 0.25 wt% of the mass of the mixed powder, and the mixture is kneaded evenly, and extruded into a clover-shaped strip in an extruder in a manner disclosed in the prior art. The formed carrier is dried at 90° C. for 3 h, then dried at 140° C. for 3 h, and then heated to 560° C. at a heating rate of 2° C. / min and kept warm for 5 h for roasting to obtain the carrier.

[0073] c. The hydrogenation active metal was impregnated according to the method of step c of Example 1, except that the precursors were nickel sulfate, ammonium metatungstate and molybdenum oxide, and 10wt% nickel, 5wt% tungsten and 5wt% molybdenum were impregnated in terms of oxides. The carrier impregnated with the hydrogenation active metal was dried at 90°C for 2h and then at 110°C for 3h to obtain a catalyst.

[0074] Example 6

[0075] The halogen-containing hydro-reforming catalyst is prepared by the following steps:

[0076] a. First, based on the mass of the mixed powder, 44wt% pseudo-boehmite, 1wt% carboxymethyl cellulose, 50wt% Y-type molecular sieve with a silicon-aluminum ratio of 11, 3wt% β molecular sieve with a silicon-aluminum ratio of 20, and 2wt% SAPO-11 molecular sieve with a silicon-aluminum ratio of 0.7 were stirred to obtain a mixed powder;

[0077] b. Then add 1wt% hydrofluoric acid, 10wt% hydrochloric acid, 9wt% hypochlorous acid, 2wt% chlorous acid, 2wt% chloric acid and 2wt% perchloric acid to the mixed powder, the amount of acid accounts for 0.05wt%, 0.1wt%, 0.1wt%, 0.1wt%, 0.05wt% and 0.1wt% of the mixed powder mass respectively, knead evenly, adopt the method disclosed in the prior art to extrude strips in an extruder, and the shape is a cylindrical strip. The molded carrier is dried at 90°C for 2h, then dried at 140°C for 2h, then heated to 580°C at a heating rate of 2°C / min and kept warm for 3h for roasting to obtain the carrier.

[0078] c. The hydrogenation active metal was impregnated according to the method of step c of Example 1, except that the precursors were nickel sulfate and molybdenum oxide, and 2 wt% nickel and 20 wt% molybdenum were impregnated as oxides. The carrier impregnated with the hydrogenation active metal was dried at 90° C. for 1 h and then at 110° C. for 2 h to obtain a catalyst.

[0079] Comparative Example 1

[0080] The halogen-free hydro-reforming catalyst is prepared by the following steps:

[0081] a. Prepare mixed powder according to the method of step a of Example 1;

[0082] b. Extrusion molding was performed according to the method in step b of Example 1, and the carrier was obtained by drying and calcining, except that the hydrochloric acid was replaced by deionized water.

[0083] c. Impregnate the hydrogenation active metal according to the method of step c of Example 1, and dry to obtain the catalyst.

[0084] Comparative Example 2

[0085] The hydro-reforming catalyst containing excess halogen is prepared by the following steps:

[0086] a. Prepare mixed powder according to the method of step a of Example 1;

[0087] b. Extrusion molding was performed according to the method in step b of Example 1, and the carrier was obtained by drying and calcining, except that the amount of acid used accounted for 3.5wt% of the mixed powder.

[0088] c. Impregnate the hydrogenation active metal according to the method of step c of Example 1, and dry to obtain the catalyst.

[0089] In order to obtain the acid distribution of the catalyst prepared by the present invention, the catalyst was subjected to NH3-TPD test, and was divided into weak acid (<200°C), medium-strong acid (200°C-400°C) and strong acid (>400°C) according to the temperature range. Each section area was integrated, and the peak area obtained can represent the acid amount. The NH3-TPD test results of Example 1, Comparative Example 1 and Comparative Example 2 are shown in Figure 1 , Table 1 is the peak area of ​​each temperature interval of the embodiment and the comparative example. From the data in the table, it can be seen that: compared with the halogen-free catalyst of Comparative Example 1, the halogen-containing catalyst of the embodiment has a higher ratio of medium-strong acid / strong acid, while the medium-strong acid / strong acid of the halogen-free catalyst of the comparative example is close to 1; and the peak of the embodiment shifts to low temperature, showing weaker acidity, which can effectively avoid the occurrence of chain breaking reaction. It is attributed to the fact that the halogen forms a weaker acid with the alumina in the carrier, thereby weakening the strong acid and increasing the proportion of medium-strong acid. Compared with Example 1, Comparative Example 2 containing excess halogen has too little strong acid, insufficient acidic sites, and low hydrogenation ring-opening activity.

[0090] Table 1: Summary of peak areas in each temperature range in the NH3-TPD spectra of Examples 1-6 and Comparative Examples 1-2

[0091] sample Weak acid peak area Medium-strong acid peak area Strong acid peak area Medium / Strong Example 1 366.3 4152.9 2460.0 1.69 Example 2 345.4 3673.6 2266.4 1.62 Example 3 295.5 3919.1 2238.6 1.75 Example 4 265.0 3183.7 2354.2 1.35 Example 5 307.2 3893.1 2521.0 1.54 Example 6 369.2 4169.3 2458.0 1.70 Comparative Example 1 19.4 3309.8 2978.6 1.11 Comparative Example 2 373.2 4399.0 1784.6 2.46

[0092] In order to verify the hydro-reforming effect of the halogen-containing hydro-reforming catalyst of the present invention on the direct coal liquefaction oil, the following activity evaluation experiment was carried out.

[0093] The specific operation steps of the activity evaluation experiment are: sieve the hydrogenation reforming catalyst, take 6 mL of 24-32 mesh, dilute the catalyst with silicon carbide particles of the same mesh, fill it into a 20 mL fixed bed reactor, and plug 1 cm of quartz wool at both ends to fix the catalyst.

[0094] First, the catalyst is wet-sulfurized at 280°C to make it in a sulfurized state, because the sulfurized hydrogenation catalyst is more active than the oxidized state. Then the crude oil is pumped into the reactor, and hydrogen is introduced at the same time. The specific reaction conditions are: reaction temperature 350°C, total reaction pressure 13MPa, liquid hourly volume space velocity 2.5h -1 , hydrogen to oil volume ratio 700.

[0095] The product oil after the reaction was collected, cut and processed, and the diesel fraction with a temperature of >165°C was taken. First, the density of the diesel fraction at 15°C was tested; then, the group composition of the diesel fraction was obtained by mass spectrometry, including the mass fractions of chain alkanes, monocyclic cycloalkanes, bicyclic and higher cycloalkanes, monocyclic aromatics, and bicyclic and higher aromatics; finally, the cetane number (CN = 68.503 + 1.029Wp - 0.287WN1 - 0.343WN2) was predicted based on the article "Prediction of the cetane number of Shenhua coal direct liquefaction diesel by hydrocarbon group composition" applicable to the properties of coal direct liquefaction oil. + -0.451WA1 -1.596*WA2 + , where Wp, WN1, WN2 + , WA1, WA2 + The mass fractions of chain alkanes, monocyclic cycloalkanes, bicyclic and higher cycloalkanes, monocyclic aromatics, and bicyclic and higher aromatics in diesel are respectively (%). The crude oil is also cut and the diesel fraction with a temperature of >165°C is taken as the reference sample.

[0096] The hydro-reforming catalysts of the embodiment and the comparative example were tested and characterized according to the above method. Compared with the comparative example 1, the catalyst containing halogen in the embodiment has a lower density of the diesel fraction and a higher hydrogenation depth, which is attributed to the fact that the appropriate amount of halogen promotes the adsorption of hydrogen by the catalyst; the predicted cetane number is larger, indicating that during the hydro-reforming process, the side chains on the ring are retained or the long carbon chain is not rearranged, which is attributed to the halogen weakening the strong acid in the catalyst, stabilizing the carbon cation, and avoiding excessive cracking or rearrangement. Compared with Example 1, the product diesel fraction obtained using the catalyst of Comparative Example 2 has a higher aromatic content and a smaller predicted cetane number, indicating that during the hydro-reforming process, the poisoning effect of excessive halogen on the catalyst exceeds the positive effect, resulting in a decrease in activity.

[0097] Table 2: Properties of feedstock and product oil

[0098]

Claims

1. A method for preparing a halogen-containing hydro-reforming catalyst, the method comprising the following steps: (1) mixing pseudo-boehmite, an extrusion aid, a molecular sieve, and optionally amorphous silicon-aluminum to obtain a mixed powder; (2) adding a halogen-containing inorganic acid to the mixed powder obtained in step (1), kneading the mixture evenly, extruding the mixture into strips in an extruder, and drying and calcining the mixture to obtain a carrier; (3) The support obtained in step (2) is impregnated in a solution formed by a hydrogenation active metal precursor, and the hydrogenation active metal is impregnated by a complex impregnation method, and the catalyst is obtained after drying. Wherein, in step (1), based on the total weight of the mixed powder, the content of pseudo-boehmite is 40wt% to 75wt%, preferably 50wt% to 70wt%; the content of amorphous silica-alumina is 0wt% to 20wt%; the content of the extrusion aid is 1wt% to 10wt%; the content of the molecular sieve is 15wt% to 55wt%; In step (2), the amount of the halogen-containing inorganic acid used is 0.2 wt% to 0.5 wt% of the mixed powder.

2. The method for preparing a halogen-containing hydro-upgrading catalyst according to claim 1, wherein: In step (3), the hydrogenation active metal is nickel and one or two selected from molybdenum and tungsten; and / or Based on the total weight of the catalyst, the content of nickel is 1wt% to 10wt% in terms of respective oxides; the content of molybdenum and tungsten is 10wt% to 40wt% in total.

3. The method for preparing a halogen-containing hydro-upgrading catalyst according to claim 1 or 2, wherein: The extrusion aid is one or more selected from carboxymethyl cellulose, citric acid, sesbania powder and guar gum; and / or In step (1), the molecular sieve is one or more selected from the group consisting of Y-type molecular sieve, β molecular sieve and SAPO-11 molecular sieve.

4. The method for preparing a halogen-containing hydro-upgrading catalyst according to claim 3, wherein: The Y-type molecular sieve has a silicon-aluminum molar ratio of 3 to 60, more preferably 5 to 30, and even more preferably 6 to 12; and / or The silicon-aluminum molar ratio of the beta molecular sieve is 20 to 45, preferably 25 to 40; and / or The SAPO-11 molecular sieve has a silicon-aluminum molar ratio of 0.4 to 0.7, preferably 0.45 to 0.

6.

5. The method for preparing a halogen-containing hydro-upgrading catalyst according to claim 3 or 4, wherein: Based on 100wt% of mixed powder, The dry basis content of the Y-type molecular sieve is 10wt% to 50wt%, preferably 20wt% to 45wt%, and more preferably 25wt% to 40wt%; and / or The dry basis content of the beta molecular sieve is 0wt% to 10wt%, preferably 2wt% to 8wt%; and / or The SAPO-11 molecular sieve content is 0wt% to 10wt%, preferably 1wt% to 8wt%.

6. The method for preparing a halogen-containing hydro-upgrading catalyst according to any one of claims 1 to 5, wherein: In step (2), the halogen-containing inorganic acid is one or more selected from hydrofluoric acid, hydrochloric acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hydrobromic acid and hydroiodic acid; and / or The concentration of the halogen-containing acid is 1 wt% to 10 wt%.

7. The method for preparing a halogen-containing hydro-upgrading catalyst according to any one of claims 1 to 6, wherein: In step (2), the drying and calcining is to dry the formed carrier at 60-90°C for 0.5-3h, then dry it at 100-160°C for 0.5-3h, and then heat it to 500-700°C at a heating rate of 1-10°C / min and keep it at that temperature for 1-5h to obtain the carrier.

8. The method for preparing a halogen-containing hydro-upgrading catalyst according to any one of claims 1 to 6, wherein: The hydrogenation active metal precursor is selected from one or more of nickel nitrate, nickel sulfate, basic nickel carbonate, molybdenum oxide and ammonium metatungstate; and / or In step (3), the drying is to dry the carrier impregnated with the hydrogenation active metal at 60-90°C for 0.5-3h, and then dry it at 100-160°C for 0.5-3h.

9. A halogen-containing hydro-reforming catalyst, which is prepared by the method for preparing a halogen-containing hydro-reforming catalyst according to any one of claims 1 to 8, In the NH3-TPD test, the ratio of the peak area integration in the range of 200 to 400°C to the peak area integration in the range of more than 400°C is 1.3 to 1.

9.

10. A method for hydrogenating and upgrading coal to directly liquefy oil, comprising the following steps: a) placing the halogen-containing hydro-reforming catalyst according to claim 9 in a sulfided state; b) subjecting the coal direct liquefaction oil to a hydrogenation reaction with hydrogen in the presence of the halogen-containing hydro-upgrading catalyst in a sulfided state obtained in step a).